ESTUDO DA INFLUÊNCIA DO DIMORFISMO SEXUAL NA LESÃO MUSCULAR DE CAMUNDONGO mdx COM DISTROFIA MUSCULAR DE DUCHENNE - Silva, Maria Cristina Salimena da (2009)
Mdx mouse, the animal model of Duchenne muscular dystrophy, lacks dystrophin and develops an X- linked recessive inflammatory myopathy characterized by degeneration of skeletal muscle fibers and replacement by connective tissue. The present work aimed to establish a possible relation of the sexual dimorphism with changes in the microenvironment of the skeletal muscle and lesion pattern at distinct phases of the myopathy. Male and female mdx and control nondystrophic C57 mice with 4 and 8 weeks of postnatal life. A group of mdx was submitted to the surgical castration: ovariectomy (OVX) and orchiectomy (OOX), and another group treated with tamoxifen, an agonist of estrogen receptor dissolved in ELVAX resin implanted locally in the right gastrocnemius muscle, with corresponding contralateral used as non-treated control muscle. Transversal sections of gastrocnemius muscle embedded in paraffin were processed for histochemistry and stained with syrius red, Giemsa, oil red, ATPase enzyme and also immunohistochemistry for identification of adhesion molecule NCAM, progenitor cells (SCA) and macrophages (Mac-1+ and F4-80). Frozen muscle fragments were processed for determination of metalloprotease MMP-2 and MMP-9 activities. Morphometric analysis showed higher percentage of mionecrose and lesser regeneration in non-operated and OOX mdx males than in both groups of females non-operated and OVX, which presented higher percentage of regenerated fibers. Mdx male and female mice did not show significant difference in the number of adipocytes in the gastrocnemius muscle, but mdx male presented less adipocytes than corresponding mdx females. Comparing to control (C57) nondystrophic mice, both male and female mdx mice, especially the castrated ones (OOX, OVX), presented higher MMP-2 and -9 activities. However, mdx intergroup analysis showed augmented MMP-9 activity in OOX males and of MMP-2 in females OVX. Comparing with the contralateral muscle, male and female mdx muscles treated with tamoxifen presented increased numbers of myofibers with membrane integrity and marked reduction of macrophages than the contralateral muscle of C57 and mdx mice. Altogether, the results indicate a beneficial effect of endogenous sexual female hormone and also the estrogen modulator receptor (tamoxifen) as therapeutic strategy capable of mitigating inflammation e myonecrosis (antiinflammatory effect), functioning as structural membrane stabilizer (sarcolemma integrity) and promoting muscle regeneration in mdx mice with Duchenne dystrophy.